On the forces that drive and resist deformation of the south-central Mediterranean: a mechanical model study. Issue 2 (12th April 2018) - Nijholt, Nicolai; Govers, Rob; Wortel, Rinus
SUMMARY: The geodynamics of the Mediterranean comprises a transitional setting in which slab rollback and plate convergence compete to shape the region. In the central Mediterranean, where the balance of driving and resisting forces changes continuously and rapidly since the Miocene, both kinematic and seismo-tectonic observations display a strong variation in deformation style and, therefore possibly, lithospheric forces. We aim to understand the current kinematics in southern Italy and Sicily in terms of lithospheric forces that cause them. The strong regional variation of geodetic velocities appears to prohibit such simple explanation. We use mechanical models to quantify the deformation resulting from large-scale Africa–Eurasia convergence, ESE retreat of the Calabrian subduction zone, pull by the Aegean slab, and regional variations in gravitational potential energy (topography). A key model element is the resistance to slip on major regional fault zones. We show that geodetic velocities, seismicity and sense of slip on regional faults can be understood to result from lithospheric forces. Our most important new finding is that regional variations in resistive tractions are required to fit the observations, with notably very low tractions on the Calabrian subduction contact, and a buildup towards a significant earthquake in the Calabrian forearc. We also find that the Calabrian net slab pull force is strongly reduced (compared to the value possible in view of the slab's dimensions) and that trench suction tractions are negligible. Such very small contributions to the present-day force balance in the south-central Mediterranean suggest that the Calabrian arc is now further transitioning towards a setting dominated by Africa–Eurasia plate convergence, whereas during the past 30 Myr slab retreat continually was the dominant factor.